The school of hard knocks: combat leadership in the American expeditionary forces - Faulkner, Richard Shawn (Kansas State University, 2008)
This dissertation examines combat leadership in the American Expeditionary Forces (AEF) in infantry and machine gun units at the company level and below to highlight the linkages between the training and professional development of junior officers and noncommissioned officers (NCOs) and the army's overall military effectiveness in World War I. Between 1865 and 1918, the growing lethality of the battlefield had forced changes to tactics and formations that placed novel demands on small unit leaders. The proliferation of new weapons in infantry companies and the thinning and extension of formations required junior officers and NCOs able to exercise an unparalleled degree of initiative and independence while also mastering new tactical and technical skills. When the United States entered World War I, the Regular Army was still grappling with how to reconcile its traditional expectations of small unit leadership with the new "skill sets" required of junior leaders in modern warfare. Faced with the need to produce officers and NCOs to lead its rapidly expanding mass army, the regulars improvised a system for identifying, training, and assigning company-level leaders. Unfortunately, the Regular Army's unpreparedness to wage a modern war, and the host of systemic problems associated with raising a mass army, meant that much of the training of these key leaders was so ill-focused and incomplete that the new officers and NCOs were woefully unprepared to face the tactical challenges that awaited them in France. These problems were only compounded when unexpected casualties among officers and NCOs in the summer and fall of 1918 led to a further curtailment in leader training the U. S. Army. The end result of the U. S. Army's failure to adequately train and develop its junior leaders was that its combat units often lacked the flexibility and "know how" to fight without suffering prohibitively high casualties. When the junior leaders failed, faltered and bungled, the AEF's battles became confused and uncoordinated slugging matches that confounded the plans and expectations of the army's senior leaders. The heavy casualties that resulted from these slugging matches further undermined the AEF's effectiveness by reducing the morale and cohesion of the army's combat units and hindering the army's overall ability to learn from its mistakes due to the high turn-over of junior officers and NCOs.
Keywords: American Expeditionary Forces; World War I; Combat Leadership; History, Modern (0582); History, United States (0337)